Review of Geoffrey D. Claussen, Alexander Green, and Alan L. Mittelman, Jewish Virtue Ethics - Michael Vanzandt Collins (Journal of Moral Theology)
Review of Geoffrey D. Claussen, Alexander Green, and Alan L. Mittelman, _Jewish Virtue Ethics_